"Sosio-Epistemologi" sebagai "Program Kritis" atas Teori Pengetahuan - Watloly, Aholiab (Jurnal Filsafat "WISDOM", 2000)
This study focuss on the existence of "Socio-epistemology" as "Critical program" of,the theories ofknowledge" The emergence ofvarious upheavals in the realm ofmodern knowledge with scientific claims that are sectorial and deterministic has had a wide spread effect on human life. The scientific situation that is so strict has forced man and the community, even culture and religion to adapt it's selftot (lily to. scientific. principles that have been stroctured in such a way as to becometheoretical instruments for total and automatic control. This worrying fact has brought about the existence of "Socio -epistemology" as "Critical program" of the theories ofknowledge . The aim ofexecuting a critical reformation and enlightenment towards the claims of sectoral knowledge, even the claims of the repressive community that· tend to perpetuate the power of the status quo as a "false consciousness ".This research aims to study is to construct a complete, whole and basicunderstanding concerning "Socio-epistemology" including its main claim as a branch of epistemology. A transcendental critique. of the theories of knowledge plus the modem social theories will be executed in order to build a Hdialectic tension" as the basic characteristic, of "Socio-epistemology". In relation to the aim and scope ofthis discussion, .' this research has been conducted using the factual historical philosophical method. The factual historical method is a method used in philosophy that .Ises a set ofsystematic principles and norms to discover, classify and process the material and also analyse in a whole, basic and critical manner.It is shown that the term "Socio-epistemology" characterises itselfas a part of critical philosophy ("critical program '') that sets itself towards optimisticenlightenment and reform. in relation. to the egoistic and ideological claims of sectoral knowledge. The main strength ofenlightenment and reform towards dialectit! illustrates'its essential character. Dialectical .roles in "Socio-epistemology" are distinctive. because of the dialectical "tension ". This dialectical tension manifests itselfin and through criticism, openness, correction, and continua/reform leading to emancipation and hypothetical consensus in the framework of praxis. As a "critical program" towards. the theory of knowledge (transcendent criticism), "Socioepistemology" tries to overcome. and release the various dogmatic rigidity that controls the· realm· ofknowledge. development under the power of "Scientism " and "Technology" or "Positivism". In this way, it is shown that knowledge is always characterised as relational and it possesses a social base including within it the interests of mankind.. On the other hand, as a critical program towards social theories (immanent criticism), "Socio-epistemology" attempts to show that man's autonomy, self consciousness ·self contemplation and man's interest within socialtheories.